The impact of specific motivation factor on purchase intentions towards Aofei Animation derivatives among Chinese university student - Ma, Yueshi; Mohd Zawawi, Julia Wirza; Mohamad, Zulkifli (Elite Scientific Publications, 2024)
Aofei Animation derivatives have become an indispensable part of China's animation industry. However, there is little literature on the impact of different uses and gratitude (U&G) on the purchase intention of Chinese college students in the dissemination process of anime derivatives. To fill this gap, this study is based on the U&G theory and aims to determine the relationship between specific U&G motivational factors and purchase intention among Chinese university students. To address this issue, we collected cross-sectional data from 347 Chinese university students, with specific types of media U&G motivation as independent variables (escape motivation, information seeking motivation, social sharing motivation, emotional motivation), and willingness to purchase Aofei anime derivatives as the dependent variable. The results indicate that specific types of media U&G, avoidance (ESP), information seeking (IS), and affective (AFF) are significantly positively correlated with purchase intention, while social sharing (SS) has no significant impact on the dependent variable. Related research can provide theoretical guidance for all relevant audiences of anime derivatives and contribute to UGT literature.